FPF: Fraud Proof Framework for Electronic Voting System - Innocent Kabandana; A.N. Nanda Kumar (Institute of Advanced Engineering and Science, 2016)
In a democratic process voting plays a vital role in selection of policy as well as candidates. Voting though gives the freedom to voter to cast his opinion it is not free fraudulent. In order to have secure voting and convey the opinion of authorized voter in this paper we have presented a java based framework for fraud proof electronic voting system. In this framework we ensure that only the authorized voter is permitted to cast his vote and mitigate illegal voters cast votes on faking or pretending to be someone else. Proposed FPF provides a multi-level of authentication mechanism to validate the voter. The proposed system is tested for efficiency and robustness in comparing it with the existing system and is found to be efficient through comparative analysis. At present FPF is successful in mitigating the unauthorized voting further enhancement in the electronic voting system is being carried out as future work.